THEORIZING SCRIPTURAL MEMORIZATION AS COGNITIVE ARCHITECTURE: A CIVILIZATIONAL-INTEGRATIVE FRAMEWORK - Najwa Azzahra; Rivo Raihan; Ina Magdalena (Senarai: Journal of Islamic Heritage and Civilization, 2026)
This study advances a civilizational re-reading of Qur’anic memorisation (tahfizh) pedagogy by exposing the structural limits of conventional methods that are largely uniform, repetitive, and insufficiently responsive to the plurality of human cognitive potentials. Within a contemporary civilizational landscape shaped by the rapid expansion of knowledge and pedagogical transformation, tahfizh can no longer remain confined to preservationist routines of rote learning; it must be rearticulated as an adaptive, integrative, and human-centered educational practice. This study seeks to formulate a renewed conceptual framework for tahfizh instruction through the integrative application of Brain Hemisphere Theory, Multiple Intelligences, and Mind Mapping as a complementary epistemological triad. Employing a descriptive-analytical method grounded in an extensive literature review, the research synthesizes primary and secondary scholarly sources, followed by critical analysis, interpretation, and conceptual generalization. The findings indicate that the integration of these three approaches constitutes a paradigmatic shift in tahfizh pedagogy, aligning it with broader civilizational dynamics. Memorisation is reconfigured from a purely mechanical exercise into a multidimensional cognitive experience that simultaneously engages logic, imagination, emotion, and visual structuring. This transformation renders the learning process more inclusive, engaging, and adaptable across diverse age groups and learning styles. In conclusion, methodological innovation in tahfizh grounded in contemporary learning theories is not merely an option but a civilizational imperative. Such an approach strengthens memory retention and deepens comprehension while opening new avenues for sustained scholarly inquiry. Ultimately, it contributes to the cultivation of a Qur’anic educational paradigm that is both rooted in tradition and dynamically responsive to the evolving demands of human civilization.